PERSEPSI DAN PARTISIPASI MASYARAKAT PETANI NELAYAN DAN PEMERINTAH DALAM PENGEMBANGAN LANSKAP AGROWISATA DI KAWASAN PESISIR (KASUS : PESISIR TELUK PACITAN - JAWA TIMUR) - Wasissa Titi Ilhami; Yoyon Haryanto (Politeknik Pembangunan Pertanian Bogor, 2020)
Indonesia is the largest archipelago in the world surrounded by large marine. In consequence, we could find many coastal region (so-called ecoton area) in this country. Ecoton area has specific character which is dynamic and susceptible, therefore it should be planned very well. Developing coastal region through tourism with appropriate and suitable planning, will bring about tourism in Pacitan Bay to be sustainable. This study aims to identify community and stakeholder perception and participation in supporting the agrotourism Landscape plan in Pacitan Bay. Community and stakeholder approach is carried out through stakeholder analysis obtained from questionnaire data, interview and literature through AHP tools. Study result shows that base on community acceptability in Pacitan Bay is potential to be a agrotourism region. The research was conducted in the gulf coast region in Pacitan. This study used descriptive quantitative approach is to do the weighting, scoring and ranking of each factor and the categories assessed. Analysis data used the AHP software Expert Choice 2000. Public perception of fisherman and the goverment in supporting the development of coastal landscape has been well proven by the value of Consistency Ratio (CR) of 0.03 which means that the perception of the development of coastal areas taking into account the social aspects of culture, ecology and the local economy.